Equity market liberalization, credit constraints and income inequality - Puyang Sun; Somnath Sen; Shujing Jin (Economics: The Open-Access, Open-Assessment E-Journal, 2013)
This paper provides compelling evidence that equity market liberalization, as the most efficient way to smooth financial market frictions such as credit constraints, can alleviate persistent cross-dynastic income inequality by promoting increased human capital accumulation. The authors examine the effect of equity market liberalization on inequality by using data from 72 countries for 1980-2006. Their measured effect is robust to alternative measures of equity market liberalization. Finally, the authors show that foreign equity flows benefit initially less-active stock markets more than the active ones, providing evidence that foreign equity flows act as a substitute for domestic financial markets. This finding emphasizes the possibility of reducing inequality and poverty through equity market liberalization.
Keywords: F41; O16; O15; O11; G0; F36; 330; income inequality; equity market liberalization; human capital; economic growth; Aktienmarkt; Deregulierung; Kapitalmarktregulierung; Wirkungsanalyse; Einkommensverteilung; Bildungsinvestition; Armut; Welt